2ax+3by=(a+2b) 3ax+2by=2(a+b)

Asked by ananyak4213277 | 17th Sep, 2021, 07:29: PM

Expert Answer:

2 a x + 3 b y = ( a + 2 b ) ...................... (1)
 
3 a x + 2 b y = 2 ( a + b ) .......................(2)
 
eqn.(1) × 3  gives ,  6 a x + 9 b y = 3 a + 6 b  .......................(3)
eqn.(2) × 2  gives ,  6 a x + 4 b y = 4 a + 4 b  .......................(4)
 
Eqn.(3) - Eqn.(4) gives ,  5 b y = 2 b - a  ,  hence  y  = ( 2 b - a ) / (5 b ) 
 
By substituting y in eqn.(1) , we get x = ( 4a + 2b ) / ( 5a )



Answered by Thiyagarajan K | 17th Sep, 2021, 07:42: PM